Proyecto de aprendizaje y el desarrollo integral de los niños de la Institución Educativa Inicial N°160 Mi Primer Aprendizaje, Caballococha 2025 - Salate Pizango, Gratelita (2025)
The main objective of this study was to explore the relationship between the implementation of learning projects and the holistic development of children at Early Childhood Education Institution No. 160 "My First Learning" during the year 2025. With a basic and quantitative approach, the research adopted a non-experimental, correlational, and cross-sectional design. The sample included 100 children, whose behaviors were recorded using a structured observation guide validated by specialists in education and child development. The analysis showed a Kendall's Tau-b coefficient of 0.653 (p < 0.001), demonstrating a positive and statistically significant association between the quality of the learning projects and the level of holistic development of the participants. These findings rejected the null hypothesis and confirmed that well-designed learning projects favorably impact the cognitive, emotional, physical, and social dimensions of children in early childhood education.